PENGARUH PROJECT BASED LEARNING (PjBL) TERHADAP KETERAMPILAN EDITING VIDEO SISWA SMK - Mitra Nata Rahayu; Fajar Arianto (Universitas Negeri Surabaya, 2023)
Project Based Learning (PjBL) is the latest learning model innovation that is deliberately designed to bridge learning theory and learning practice, especially those related to creativity, work design in the form of projects oriented towards product and concept acquisition and to improve learning outcomes in the form of students' video editing skills. This study aims to determine the effect of the Project Based Learning (PjBL) learning model on video editing skills in Audio Video Processing Engineering subjects. The research used a quasi-experimental design with a posttest only control group design. The research subjects were students of Multimedia Department Vocational High School totaling 68 students. Data collection was carried out tests for video editing skills. The research hypothesis was tested using t-test. Descriptive statistics research results show the average value of video editing skills of students who apply the Project Based Learning (PjBL) learning model reaches 82.53 while those who learn using direct learning (Direct Learning) is 74.15. The results of the research hypothesis show that the difference between the two numbers shows a significant difference in the results of video editing skills